Les Cenci e il don Giovanni: traduzione, (ri)configurazione e “scarto” in una novella Stendhaliana (Altre Modernità, 2020)
On July 1st, 1837, Stendhal publishes a novella, Les Cenci, in La Revue des Deux Mondes. He deliberately proposes an arbitrary translation of a text from the Roman manuscript of Palazzo Caetani (BNF, Ms Italien 172). Stendhal, who is not new to translation, has already published a novella from the manuscripts, and he progressively evolves into a re-writing of the original text. Nevertheless, in Les Cenci he is still faithful to the original text and the new text shows up the first signals of a paradigmatic change, e.g. the long introduction. Textual occurrences, marks of additions or "flotsams" from the manuscript, point out his poetics of translation. My purpose is to highlight how some of these text "flotsams" are the symptom of a poetics of mystification, which in turn identifies his poetics of enunciation and reception. Eventually, a pragmatic analysis connected to textual deictics, to the enunciative scene and to textual “flotsams” can be useful to understand the whole text construction and the (dis)concordance between the fictional and the real world. Furthermore, it can show up how the text reorganization is the result of a (re)configuration: the “literary myth” of Don Giovanni.